Implementasi Teknologi Blockchain dalam Digital Marketing - Solechan, Achmad; Abidin, Rohmad (Universitas PGRI Semarang, 2024)
This research was conducted because many parties feel that their privacy has been invaded as marketers. collecting internet user data. Some respondents were concerned about their privacy on the use of digital marketing, especially the abuse of their privacy related to user data. The size of the blockchain technology market worldwide in 2018 to 2025, where it is estimated that in 2025, the blockchain technology market will have a size of 39.7 billion. The graph shows the blockchain market prediction which also shows the adoption of the use of blockchain technology. Therefore, this study aims to determine the implementation of blockchain in the world of digital marketing in a literature review study.Â This study uses a qualitative method with a literature review technique with the results discussing 26 published research articles relevant to this research. The research results show that blockchain has great potential in digital marketing, especially in increasing trust, transparency, and efficiency. However, the adoption of this technology faces challenges in the form of technological literacy and significant investment. A mature implementation strategy is needed to fully utilize the potential of blockchain in the digital marketing sector.